3-aminoquinoline: a turn-on fluorescent probe for preferential solvation in binary solvent mixtures. (1st July 2022) - Das, Sharmistha; Das, Shirsendu; Singh, Avinash Kumar; Datta, Anindya
Abstract: 3-Aminoquinoline (3AQ) has been used as a fluorescent probe for preferential solvation in hexane-ethanol solvent mixtures. Results of the present experiment have been put into context by comparison with prior observations with 5-aminoquinoline (5AQ) as the probe. 3AQ exhibits a relatively small change of dipole moment (Δ μ = 2.2 D) upon photoexcitation, compared to 5AQ (Δ μ = 6.1D), which might appear to be a hindrance in the way of its use as a solvation probe. Indeed, the values of parameters like spectral shifts are smaller for the present experiment with 3AQ. At the smallest concentration of alcohol used, its local mole fraction around the probe is significantly lower than in the previous experiments with 5AQ. However, these apparent disadvantages are outweighed by the significant increase in fluorescence intensity and lifetime observed with increasing concentration of ethanol in the solvent mixture, as opposed to the drastic fluorescence quenching that occurs for 5AQ. This is a marked advantage in the use of 3AQ in studies like the present one. The local mole fraction of ethanol and preferential solvation index experienced by 3AQ are in line with those reported for 5AQ. The disadvantage of the smaller magnitude of Δ μ persists in the time resolved fluorescence experiments, for solvent mixtures with very low ethanol content. Negligible wavelength dependence of fluorescence transients of 3AQ is observed for x p = 0.002, . However, this effect is outweighed at higher alcohol concentrations, for which nanosecond dynamics of preferential solvation is observed.